Relevance of Electronic Resources and Improvement of Access for Effective Distance Learning and Continuing Education Programme - Wisdom O. Anyim (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This paper investigates the relevance of electronic resources and improved access for effective distance learning and continuing education. The descriptive survey design was adopted for the study. The total population of the study comprises 7,125 registered students of the National Open University of Nigeria. A convenience sampling technique was used to select a sample size of 379 respondents. Structured questionnaires were distributed to the respondents through a research assistant, and only 320 valid responses were returned and used for the study. The study used frequency counts and percentages as statistical measures for data analysis. Findings revealed that students access e-resources regularly. Electronic resources were also relevant as they provide students with up-to-date information, complete information from different sources, speedy and easy access to information, and more. Access to electronic resources can be improved through the following means: provision of useful Internet/server to enhance the accessibility of e-resources, online user guideline for accessing e-resources, creation of user-friendly interfaces for easy access to online contents. It was recommended that audio and video conference chats be made available to students to connect librarians for assistance when the need arises; compulsory user-education and orientation program should also be conducted for students on the use of electronic resources.